Pluralisms in Truth and Logic (Palgrave Innovations in Philosophy, 2018)
"This volume has a stellar lineup, with major players and major positions all represented well. It is essential reading for anyone interested in pluralism about truth and/or pluralism about logic." - Stewart Shapiro, O'Donnell Professor of Philosophy, Ohio State University, U.S.A. "This is a superb collection of new articles on a cluster of exciting and timely topics: pluralism in truth, pluralism in logic, and the connections between them. The collection provides a vivid, state-of-the-art picture of these issues. Highly recommended!" -Gila Sher, Professor of Philosophy, University of California, San Diego, U.S.A. This edited volume brings together 18 state-of-the art essays on pluralism about truth and logic. Parts I and II are dedicated to respectively truth pluralism and logical pluralism, and Part III to their interconnections. Some contributors challenge pluralism, arguing that the nature of truth or logic is uniform. The majority of contributors, however, defend pluralism, articulate novel versions of the view, or contribute to fundamental debates internal to the pluralist camp. The volume will be of interest to truth theorists and philosophers of logic, as well as philosophers interested in relativism, contextualism, metaphysics, philosophy of language, semantics, paradox, epistemology, or normativity. Jeremy Wyatt is Assistant Professor of Philosophy, Underwood International College, Yonsei University, Incheon, South Korea. His main research interests are the philosophy of language, metaphysics, and truth. Nikolaj J. L. L. Pedersen is Associate Professor of Philosophy and Director of the UIC Research Institute and Veritas Research Center, Underwood International College, Yonsei University, Incheon, South Korea. His main research areas are truth, epistemology, and metaphysics. Pedersen is a co-editor of New Waves in Truth (2010), Truth and Pluralism: Current Debates (2013), Epistemic Pluralism (2017), Epistemic Entitlement (2019), and The Routledge Handbook of Social Epistemology (2019). Nathan Kellen works at the Department of Philosophy, University of Connecticut, USA. Kellen's work is on truth, the philosophy of logic, philosophy of mathematics and ethics.